Antipyretic Plants: An Updated Review - Garg, Vandana; Dutt, Rohit (Current Bioactive Compounds, 2020)
Background: Fever, is known as pyrexia, may occur due to infection, inflammation, or any tissue damage and disease states. Normally, the infected or damaged tissue initiates the enhanced formation of pro-inflammatory mediators like cytokines which further increases the synthesis of prostaglandin E2 (PgE2) near the hypothalamic area and thereby trigger the hypothalamus to elevate the body temperature. Objective: Antipyretics are the agents which reduce the elevated body temperature. The most commonly used antipyretic agent, paracetamol, may be fatal due to its side effects. Methods: In this review paper, Chemical Abstracts, Google Scholar, PubMed, and Science Direct were the sources for the published article to collect information regarding antipyretic activity. Results: This review compiles the antipyretic plants that may be useful to treat fever due to various diseases. Conclusion: These medicinal plants could be good alternatives for traditional allopathic antipyretics.
Keywords: antibiotics